Consumer perspectives on the therapeutic value of a psychiatric environment - Donald, F.; Duff, Cameron; Lee, S.; Kroschel, J.; Kulkarni, J. (2015)
© 2015 Shadowfax Publishing and Informa UK Limited All rights reserved: reproduction in whole or part not permitted. Background: Existing reports of the environmental aspects of recovery from mental illness have been confined to consideration of community spaces and the natural environment. Aims: This paper aims to extend this literature by assessing the role of psychiatric settings in recovery. Methods: Nineteen inpatients from the psychiatric unit of a large inner city hospital in Melbourne, Australia, took part in the study, which involved semi-structured interviews and focus groups. Results: Analysis identified three major themes concerning consumers' experience within the unit: the importance of staff; lack of clear architectural identity resulting in confused or confusing space; and limited amenity due to poor architectural design. Conclusions: These findings have important implications for the delivery of care in psychiatric environments in ways that promote well being within these settings, and align with relevant mental health policy recommendations.